Formulasi dan Uji Aktivitas Antibakteri Sediaan Mouthwash Fraksi Metanol Daun Seledri (Apium graveolens L.) terhadap Pertumbuhan Bakteri Streptococcus mutans Penyebab Karies Gigi - Zulhijjati, Mirzalina; Yuliana, Tri Puspita; Fatmayanti, Baiq Risma; Oktresia, Erma Ewisa (Sinteza, 2026)
Streptococcus mutans is a bacterium found in the human oral cavity and is the primary cause of tooth decay. The effects of Streptococcus mutans bacteria can be eliminated with mouthwash formulated with natural ingredients, one of which is celery leaves, which are known to have antibacterial properties against the growth of Streptococcus mutans. The purpose of this study was to determine the best concentration of a mouthwash formulation using the methanol fraction of celery leaves based on the results of the physical properties evaluation test and to determine the antibacterial activity of a mouthwash formulation using the methanol fraction of celery leaves in inhibiting the growth of Streptococcus mutans bacteria. This study was a quantitative study using a laboratory experimental method with a posttest-only control group design. This study is a quantitative study using a laboratory experiment method with a posttest-only control group design by observing the area of ​​the inhibition zone as the dependent variable. The area of ​​the inhibition zone of each formula was compared with the control using the ANOVA test. The results of the physical properties evaluation test, including ogrnanoleptic tests, pH tests, homogeneity tests, specific gravity tests, and cycling tests, met the requirements for good physical quality. The highest antibacterial activity results were found in formula III with a concentration of 1.5% celery leaf methanol fraction with an average inhibitory power of 23.63 mm with a Very Strong category.